"Inclusive business" in agriculture: Evidence from the evolution of agricultural value chains. (October 2020) - German, Laura A.; Bonanno, Anya M.; Foster, Laura Catherine; Cotula, Lorenzo
Highlights: We critically examine the concept and practice of inclusive business by analysing evidence across agricultural value chains. Structural factors constrain space for inclusiveness, leading to growing ex clusion for smallholders and employees. The "inclusive business" concept obscures these factors by focusing attention on the behavior of individual businesses. Inclusive agrarian trajectories hinge on a re-think of the role played by public policy, finance and gate-keeper functions. Abstract: Sustained interest by the business community in commercial agriculture in the global South has been welcomed for its potential to bring capital into long neglected rural areas, but has also raised concerns over implications for customary land rights and the terms of integration of local land and labor into global supply chains. In global development policy and discourse, the concept of "inclusive business" has become central in efforts to resolve these tensions, with the idea that integrating smallholders and other disadvantaged actors into partnerships with agribusiness firms can generate benefits for national economies, private investors, and local livelihoods. Scholarly treatment of the topic has tended to be polarized into win/lose narratives, or points to the contingency and social differentiation of localized experiences. This review paper takes a different approach, exploring published evidence on the structural factors shaping agricultural value chains and their implications for social inclusion. We develop a typology of seven agricultural value chains, and use this to select a sample of crops in specific world regions for an analysis of how structural factors in value chain relations - from crop features, to market dynamics and policy drivers – affect social inclusion (and exclusion). Such an approach allows us to ask whether inclusive agribusiness is a realistic goal given the broader structuring of agribusiness and the global economic system. Our study finds that while the characteristics of specific crops and supply chains exert a strong influence on opportunities and constraints to inclusion, the overall trend is towards more ex clusive agribusiness as governments scale back support to smallholders, more stringent standards raise barriers to entry, and firms streamline operations to enhance competitiveness. This raises questions about the feasibility of this goal under the current political economic system. Findings point to the need to re-consider the policy choices behind these trends, and how we deploy the fiscal, legislative, and gate-keeper functions of the state to shape agrarian trajectories.